2013
DOI: 10.1590/s2176-94512013000500011
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to orthodontic treatment time in adult patients

Abstract: Introduction:The length of time that it takes an orthodontist to treat adult patients varies widely. Objective: The aim of this study was to investigate how different variables influence treatment time. Methods: Seventy clinical case reports of successfully treated adult patients were examined. The patients were selected from 4,723 records held by three experienced orthodontists. The influence exerted by the following variables on treatment time was assessed: age, sex, facial pattern, severity of malocclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 18 publications
8
46
1
1
Order By: Relevance
“…Appliance breakages were weak, but statistically associated with treatment time in this study (R 2 =0.0596), as previously described 6,16,20 . Increments in treatment duration might be due to the necessity of returning to a lighter arch wire or the impossibility of treatment evolution in that month.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Appliance breakages were weak, but statistically associated with treatment time in this study (R 2 =0.0596), as previously described 6,16,20 . Increments in treatment duration might be due to the necessity of returning to a lighter arch wire or the impossibility of treatment evolution in that month.…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports evaluating adult patients 16 showed that the amount of missed appointments is the factor that affects treatment duration (43.75%) of Class I and Class II patients the most. These findings are supported by our findings (43.49%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The best scientific evidence now available indicates that the type of malocclusion, clinical decisions and patient compliance 3 - 5 have more importance than the technique or bracket used 4 6 , 7 Therefore, altering "technique-sensitive" features can hardly improve efficiency or reduce treatment time, unless these features are common to all techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients under exodontia require a longer period of time (4). The longer the treatment course is, the greater the risks of gingivitis, enamel demineralization, decayed tooth, and even root resorption (56).…”
Section: Introductionmentioning
confidence: 99%